2010
DOI: 10.1111/j.1755-3768.2009.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

A study comparing ocular pressure pulse and ocular fundus pulse in dependence of axial eye length and ocular volume

Abstract: ABSTRACT.Purpose: There is a long-standing discussion about whether myopia is associated with decreased choroidal blood flow, as suggested by pneumotonometric measurements of pulsatile ocular blood flow (POBF). However, it has been noted previously that calculations of POBF depend on intraocular volume. Methods: In the present study we investigated this volume dependence through the comparison of ocular pressure pulse and ocular fundus pulse. Fifty-one healthy participants with different refractive errors part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
2
26
1
4
Order By: Relevance
“…10,[12][13][14] Recent work has shown that the increase in ocular size in myopia is found in all planes ( [12][13][14], although the enlargement is largest in the axial plane. 14,15 It is well established that ocular rigidity (OR) is reduced in larger myopic eyes compared with emmetropic [16][17][18][19] and hyperopic eyes. 16,17,20 The low OR found in myopia is associated with weakening and reduced tensile strength of the sclera 19,21,22 and is due primarily to a thinning of collagen fiber bundles and a reduction in the size of the individual collagen fibrils.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,[12][13][14] Recent work has shown that the increase in ocular size in myopia is found in all planes ( [12][13][14], although the enlargement is largest in the axial plane. 14,15 It is well established that ocular rigidity (OR) is reduced in larger myopic eyes compared with emmetropic [16][17][18][19] and hyperopic eyes. 16,17,20 The low OR found in myopia is associated with weakening and reduced tensile strength of the sclera 19,21,22 and is due primarily to a thinning of collagen fiber bundles and a reduction in the size of the individual collagen fibrils.…”
mentioning
confidence: 99%
“…14,15 It is well established that ocular rigidity (OR) is reduced in larger myopic eyes compared with emmetropic [16][17][18][19] and hyperopic eyes. 16,17,20 The low OR found in myopia is associated with weakening and reduced tensile strength of the sclera 19,21,22 and is due primarily to a thinning of collagen fiber bundles and a reduction in the size of the individual collagen fibrils. 19,22 Relatively little work has been done to examine whether these variations in OR influence the dynamic characteristics of saccadic eye movements.…”
mentioning
confidence: 99%
“…Το εύρημα αυτό έχει περιγραφεί σε αρκετές μελέτες σε μεγάλο αριθμό ασθενών. [149][150][151][152] Σε μία μελέτη σε 376 οφθαλμούς, περιγράφηκε επίσης η μείωση του ΟΕΠ με την αύξηση του ΑΜ, 149 αλλά παράλληλα οι συγγραφείς ανέφεραν ότι από τις μετρήσεις τους δεν προέκυπτε συσχέτιση μεταξύ ΟΕΠ και οφθαλμικής ακαμψίας, σε αντίθεση με τα αποτελέσματα της παρούσας μελέτης. Η διαφορά αυτή είναι δυνατό να οφείλεται σε διαφορές στη σύνθεση του δείγματος στις δύο μελέτες, αλλά και στη διαφορετική προσέγγιση του τρόπου μέτρησης της οφθαλμικής ακαμψίας, αφού η επεμβατική μέτρηση που ακολουθήθηκε στην παρούσα μελέτη προσφέρει και τη μεγαλύτερη ακρίβεια.…”
Section: σχέση οφθαλμικού εύρους παλμού με το αξονικό μήκοςunclassified
“…Μειωμένες τιμές ΣΟΡ σε ασθενείς με μυωπία έχουν επισημανθεί σε παλαιότερες μελέτες στη βιβλιογραφία με τη χρήση της τεχνικής της πνευμοτονομετρίας. 151,152,159,202 Σε όλες αυτές τις μελέτες προέκυπτε στατιστικά σημαντική συσχέτιση μεταξύ ΣΟΡ και ΑΜ, με μέτριου μεγέθους συντελεστές συσχέτισης. Μάλιστα, σε μία μελέτη πάνω στους παράγοντες που είναι δυνατό να σχετίζονται με το μέγεθος της ΣΟΡ σε 80 φυσιολογικούς ασθενείς, το ΑΜ ήταν η μόνη παράμετρος η οποία εμφάνιζε στατιστικά σημαντική θετική συσχέτιση με τη ΣΟΡ, ενώ η ηλικία, η ΣΑΠ και η ΔΑΠ, η ΕΟΠ και το διαθλαστικό σφάλμα δεν ήταν σημαντικές παράμετροι στο μοντέλο.…”
Section: σχέση σφύζουσας αιματικής ροής με το αξονικό μήκοςunclassified
“…Como o cone de medição é mantido em contato com os olhos por alguns segundos, o aparelho pode gravar simultaneamente as flutuações hemodinâmicas permanentes da PIO sob a forma de uma curva tensional que registra a recorrente pressão sistólica (PAS) e diastólica (PAD) e a sua diferença, ou seja, APO 10, (Detry-Morel et al, 2007;Sullivan-Mee et al, 2007;Carbonaro et al, 2008;Stalmans et al, 2008), que tem sido apontada como indicador indireto da perfusão da coroide (Hoffmann et al, 2004;Punjabi et al, 2006;Detry-Morel et al, 2007Carbonaro et al, 2008;Erickson et al, 2009;Villas-Bôas et al, 2009) e da reflexão do fluxo sanguíneo ocular correspondente à pulsação cardíaca em função do tempo (Hoffmann et al, 2004;Punjabi et al, 2006;Stalmans et al, 2008;Villas-Bôas et al, 2009;Berisha et al, 2010). Portanto, a APO pode refletir mudanças volumétricas que são dependentes no fluxo sanguíneo ocular.…”
Section: O Tonômetro De Contorno Dinâmico (Tonômetro De Pascal Suíçaunclassified